PERSEKONGKOLAN TENDER DALAM PERSAINGAN USAHA MENURUT UU NO. 5 TAHUN 1999 TENTANG LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Dewi Nawang Wulan; Ainul Masruroh; rusydi rusydi (universitas islam darul ulum lamongan, 2019)
Conspiracy tender an action collusive which can reduce the transparency and honesty among the participants of the tender. While time is the government is already set on Procurement of Goods and / or Services in electronic form of e-tendering, with the system online are expected to minimize leakage of the tender as well as the level of conspiracy tender there . But in practice leakage tender and conspiracy are still going on between the actors of business , including the Tender Works Revitalization Development Arena Youth / Teens province of West Nusa Tenggara on Year Budget 2011. Setting the tender which already are online should be able to prevent the conspiracy that happen, but in practice conspiracy tender occur with other modes namely with an agreement that is done by the participants of the tender kolusif the form of similarity IP Address, is practices outside the mechanism system of tendering set . Of things that mean conspiracy tender is still going on and still be one of the problems for the world of busines . Material laws are used as a reference will be analyzed using the technique of analysis of the contents by formulating the analysis of the decision that was decided by the Commission for the Supervision of Competition Usaha (KPPU). Results of the study showed that the system electronics have not fully guarantee the tender free of the conspiracy that carried out by the perpetrators of the business . It is an impact on the budget and the level of competition of business that is healthy , from the system electronics in the form of e- tenderimg the search of a conspiracy can be detected much earlier.